Is the Laparotomy Here to Stay? A Review of the Disadvantages of Laparoscopy - Gulack, Brian C.; Wong, Kaitlyn; Sparks, Eric; Ramjist, Joshua; Zhu, Haitao; Pierro, Agostino (European Journal of Pediatric Surgery, 2020)
Minimally invasive procedures have seen increasing utilization in the pediatric patient population since the 1990s. Most thoracic and abdominal operations in pediatric surgery can be performed in a minimally invasive manner including those performed in neonates and infants. Thoracoscopic or laparoscopic operations can reduce hospital length of stay, minimize postoperative pain, and lead to more aesthetic results. However, it is important to be aware of the inherent risks, limitations, and adverse effects associated with these thoracoscopic and laparoscopic techniques, particularly in special populations. In this article, we will review the risks and limitations of laparoscopy in pediatric patients such as cost, operative time, reduced effectiveness, air embolism, hypercarbia, hypothermia, and access-related injuries.
Keywords: laparoscopy; minimally invasive surgery; pediatric surgery